2020
DOI: 10.1192/bjb.2020.96
|View full text |Cite
|
Sign up to set email alerts
|

Impact of homicide by a psychiatric patient on forensic psychiatrists: national survey

Abstract: Aims and method To explore the experiences and support needs of consultant forensic psychiatrists, whose patients had committed homicide while under their care. We circulated a survey to all forensic psychiatrists in the UK, through the Royal College of Psychiatrists, asking about their experiences of a homicide by a patient under their care. Respondents were invited to discuss their experiences further in a structured telephone interview and themes were identified from these discussions. Data were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(45 citation statements)
references
References 19 publications
(27 reference statements)
4
41
0
Order By: Relevance
“…Previous research has shown that psychiatrists can be reluctant to seek support after a patient suicide or homicide [ 6 , 26 ]. Brooks et al [ 27 ] have identified multiple barriers to doctors seeking help for mental health including anticipated negative career implications from either taking time off work or in disclosing their condition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has shown that psychiatrists can be reluctant to seek support after a patient suicide or homicide [ 6 , 26 ]. Brooks et al [ 27 ] have identified multiple barriers to doctors seeking help for mental health including anticipated negative career implications from either taking time off work or in disclosing their condition.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of homicide carried out by patients are lower, averaging 54 a year [ 3 ], but the personal and professional repercussions of such an event appear both more common and more severe. In a survey assessing the impact of patient homicide on forensic psychiatrists, 81% of respondents said the experience had impacted their mental health, 25% of which described it as ‘very significant’ [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations